2013
DOI: 10.1016/j.eurpsy.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Remission of positive symptoms according to the “remission in Schizophrenia Working Group” criteria: A longitudinal study of cognitive functioning

Abstract: Schizophrenia patients in positive symptomatic remission (PSR; n=39) were assessed using a longitudinal research design. The patients were found to exhibit widespread cognitive impairments that were stable over the three-year follow-up period. The findings support a generalized and stable cognitive impairment profile among schizophrenia patients in partial symptomatic remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…First, we showed that both at baseline and at follow-up, patients who obtained RSWG remission status functioned better in terms of global functioning, unmet needs and QoL, which is in line with earlier findings and supports the validity of the RSWG remission criteria (Barak and Aizenberg, 2012; Braw et al, 2012; Chang et al, 2012; Ciudad et al, 2009; De Hert et al, 2007; Eberhard et al, 2009; Lambert et al, 2010; Van Os et al, 2006). Another interesting finding was that we found an association between younger age at baseline and remission status at follow-up, indicating that increasing age at study entry is associated with a greater risk not to reach remission.…”
Section: Discussionsupporting
confidence: 90%
“…First, we showed that both at baseline and at follow-up, patients who obtained RSWG remission status functioned better in terms of global functioning, unmet needs and QoL, which is in line with earlier findings and supports the validity of the RSWG remission criteria (Barak and Aizenberg, 2012; Braw et al, 2012; Chang et al, 2012; Ciudad et al, 2009; De Hert et al, 2007; Eberhard et al, 2009; Lambert et al, 2010; Van Os et al, 2006). Another interesting finding was that we found an association between younger age at baseline and remission status at follow-up, indicating that increasing age at study entry is associated with a greater risk not to reach remission.…”
Section: Discussionsupporting
confidence: 90%
“…Risperidone LAI should be investigated for other recovery aspects of schizophrenia, since patients in RSWG-remission have a better cognitive outcome [ 19 , 20 ] and quality of life [ 21 , 22 ], but may perceive a decreased sense of wellbeing [ 23 ]. In addition, Rocca et al [ 24 ] reported that second generation antipsychotic use predicts better social functioning and better executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the studies included participants with a diagnosis of schizophrenia only Braw et al, 2013;Kontis et al, 2013;Pantelis et al, 1997a;, three included a diagnosis of schizophrenia, schizophreniform or schizoaffective disorder Joyce et al, 2002;Leeson et al, 2009a), two included schizophrenia or other non-affective psychotic disorder Fagerlund et al, 2006) and one specified "schizophrenia or non-organic and non-affective psychosis" (Saleem et al, 2013). Of the 11 eligible studies (see Table 1), two included some of the same participants Braw et al, 2013) but the studies were separately analysed as different variables were reported: 5-move variables were reported in one of the studies while composite variables were reported in the other. Another of the eligible studies failed to report thinking latencies and included some data previously reported in a prior study.…”
Section: Selection Of Articlesmentioning
confidence: 99%